2008
DOI: 10.3349/ymj.2008.49.3.372
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Posttraumatic Stress Disorder and Mental Health in Women Who Escaped Prostitution and Helping Activists in Shelters

Abstract: PurposeThis study compared the mental symptoms, especially symptoms of posttraumatic stress disorder (PTSD), of women who escaped prostitution, helping activists at shelters, and matched control subjects.Materials and MethodsWe assessed 113 female ex-prostitutes who had been living at a shelter, 81 helping activists, and 65 control subjects using self-reporting questionnaires on demographic data, symptoms related to trauma and PTSD, stress-related reactions, and other mental health factors.ResultsFemale ex-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The high rates of violence and association with depression and anxiety are consistent with the literature. 4,12,19 The relationship between violence and mental illness is complex. It is unclear whether the experience of violence itself can cause mental disorders or that those with mental illness are more vulnerable and more likely to experience violence.…”
Section: Role Of Child Abuse Violence and Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…The high rates of violence and association with depression and anxiety are consistent with the literature. 4,12,19 The relationship between violence and mental illness is complex. It is unclear whether the experience of violence itself can cause mental disorders or that those with mental illness are more vulnerable and more likely to experience violence.…”
Section: Role Of Child Abuse Violence and Stigmamentioning
confidence: 99%
“…They are also a vulnerable population group as they are often exposed to high rates of violence from police, brothel owners and clients and they are exposed to health risks such as human immunodeficiency virus (HIV) infection and sexual harassment. 4,5 Violence amongst sex workers is a common occurrence. 3,5,6 Several studies have documented the high prevalence of violence amongst sex workers and its association with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse physical health. Worldwide, the impacts of alcohol use on physical health conditions of FSWs have been largely neglected including fatigue and sleep problems (Jung et al, 2008). Alcohol-related conditions (i.e.…”
Section: Impacts Of Alcohol Usementioning
confidence: 99%
“…A few studies reported the association between alcohol use and mental health. Ex-FSWs in Korea had frequent and serious posttraumatic stress disorder symptoms, which were positively correlated with drinking problems (Jung et al, 2008). Alcohol intoxication was significantly associated with suicidal ideation among establishmentbased FSWs in a rural county of China (Hong et al, 2007a).…”
Section: Impacts Of Alcohol Usementioning
confidence: 99%
“…In medicine, it is accepted that there is heterogeneity in the capacity of people with psychiatric and cognitive disorders to consent to medical treatment or research [33,34], and special protections are put in place to safeguard them. People with psychiatric and cognitive disorders also sell sex [35] and might even be overrepresented among sellers [36]. Some sellers also drink and use drugs and therefore might be impaired when negotiating paid sexual encounters.…”
Section: Fundamental Ethical Problems In Commercial Sex Policy Decisimentioning
confidence: 99%